Élaboration et expérimentation d’un modèle intégrateur en accompagnement professionnel dans le cadre d’une recherche-action-formation - Bezeau, David; Turcotte, Sylvain; Beaudoin, Sylvie; Grenier, Johanne (Canadian Journal of Education/Revue canadienne de l'éducation, 2020)
This research experiments an innovative integrative model of professional support in collaboration with two health and physical education teachers. The objectives of this article are to describe: 1) the modifications made to the model by the participants and 2) the strengths and the elements to improve this process. To meet these objectives, two methods of data collection were used in a collaborative action research: 1) group interviews and 2) logbooks. The main finding is that this professional development device has several strengths, but requires a significant commitment from the participants. Keywords: professional support, professional development, collaborative action research, health education, health and physical education